Faktor-Faktor yang Memengaruhi Intensitas Perilaku dalam Penggunaan E-Filing Pada Wajib Pajak Orang Pribadi - Dewi, Putu Dessy Kurnia; Noviari, Naniek (E-Jurnal Akuntansi; Vol 22 No 3 (2018)DO - 10.24843/EJA.2018.v22.i03.p27, 2018)
This study aims to determine the intensity of behavior in the use of e-filing in Badung regency, measured through the perception of usability, perception of ease, security and confidentiality, preparedness of taxpayer information technology, and experience. The intensity of behavior in the use of e-filing is desire to use e-filing and reuse it in the future. This research was in Badung regency. The number of samples as 100 taxpayers personal users e-filing. The method of the sample using purposive sampling, the technique of determining the sample by using certain criteria that have been determined in accordance with the purpose of study. Data collection was questionnaires. The analysis technique used is multiple linear regression analysis. Based on the results concluded that the perception of usability, perception of ease, security and confidentiality, readiness of taxpayer information technology influential, and experience positively affect the intensity of e-filing user behavior. Keyword : Intensity of behavior, e-filing, individual taxpayer, Annual SPT.